2015
DOI: 10.1159/000374033
|View full text |Cite
|
Sign up to set email alerts
|

GFP Labeling and Hepatic Differentiation Potential of Human Placenta-Derived Mesenchymal Stem Cells

Abstract: Background: Stem cell-based therapy in liver diseases has received increasing interest over the past decade, but direct evidence of the homing and implantation of transplanted cells is conflicting. Reliable labeling and tracking techniques are essential but lacking. The purpose of this study was to establish human placenta-derived mesenchymal stem cells (hPMSCs) expressing green fluorescent protein (GFP) and to assay their hepatic functional differentiation in vitro. Methods: The GFP gene was transduced into h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Green fluorescent protein (GFP) has been used to evaluate cellular engraftment and for long-term cell tracking [ 3 , 4 ]. Our previous studies showed that transfection of human placental mesenchymal stem cells (hPMSCs) with the GFP gene did not affect their viability, phenotype profile, or pluripotency [ 5 ]. However, the impact of GFP labeling on the metabolism of MSCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Green fluorescent protein (GFP) has been used to evaluate cellular engraftment and for long-term cell tracking [ 3 , 4 ]. Our previous studies showed that transfection of human placental mesenchymal stem cells (hPMSCs) with the GFP gene did not affect their viability, phenotype profile, or pluripotency [ 5 ]. However, the impact of GFP labeling on the metabolism of MSCs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are not only observed in in-vitro conditions but also in some in-vivo small animal studies, which have revealed the transformation (differentiation) of the MSCs into adult lineages [68]. These are further explained with the presence of the tracker-like GFP [69], indicating the newly formed cells with the presence of the GFP. In human studies, many types of the MSCs expressing pancreatic duodenal homeobox 1 (Pdx1) gene have been shown to differentiate into insulin-producing cells or functions of pancreatic β cells [70].…”
Section: Mechanism Behind the Mesenchymal Stem Cell Repairmentioning
confidence: 70%
“…Previous studies have shown successful transduction using lentiviral vectors encoding fluorescent proteins in human adipose-derived stem cells with potential for adipogenic and osteogenic differentiation [32] and in human placenta-derived MSCs with potential for adipogenic, osteogenic, and hepatic differentiation [33]. In a recent study, Ovchinnikov et al used a lentiviral-based delivery system to generated transgenic pluripotent stem cells (PSC) lines that expressed pluripotency-driven GFP [13].…”
Section: Discussionmentioning
confidence: 99%